Penerapan Etika dalam Asesmen Psikologi di Bidang Bimbingan dan Konseling - Adhelea Satsabhila (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Psychological assessment is an important part of guidance and counseling services because it helps counselors understand the conditions and needs of their clients more accurately. However, its implementation must adhere to ethical principles, such as maintaining confidentiality and being objective in assessment. This article aims to discuss the importance of ethics in the psychological assessment process, particularly in the context of guidance and counseling services in schools. Using a literature review method, this article examines various literature related to ethical codes, assessment principles, and challenges frequently faced by counselors. The findings indicate that counselors must understand the boundaries of their authority in using assessment tools, maintain the confidentiality of clients' data, and continuously develop their professional competencies. By applying appropriate ethics, assessments can be conducted fairly, accurately, and maintain clients' trust in counseling services.